2017
DOI: 10.1093/europace/eux268
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of athletes with cardiac disorders: a new paradigm

Abstract: Athletes with cardiac disorders frequently pose an ethical and medical dilemma to physicians assessing their eligibility to participate in sport. In recent decades, patient empowerment has been gaining increasing recognition in clinical decision-making. Empowerment is a process through which people are involved over the decisions and actions that affect their own lives. In the context of a cardiac disorder, empowerment means giving an athlete the chance to participate in the decision about whether or not to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Another study also found that any 1-metabolic equivalent (MET) increase in cardiorespiratory fitness could reduce the risk of AF by 7% (1 MET = a whole-body oxygen consumption of 3.5 mL O2/kg/min) [21]. Also, in other studies in the United States and Norway, results are also in favor of the effectiveness of exercise in reducing the incidence of AF [1,5,22,23]. Although many population-based studies have been carried out so far, we still cannot see a very precise model for estimating the effect of minimal physical activity, depending on its condition and type, in relation to AF risk; however, the beneficial effects of exercise are unobtainable on the overall pattern of heart disease risk.…”
Section: Studies In the General Populationmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study also found that any 1-metabolic equivalent (MET) increase in cardiorespiratory fitness could reduce the risk of AF by 7% (1 MET = a whole-body oxygen consumption of 3.5 mL O2/kg/min) [21]. Also, in other studies in the United States and Norway, results are also in favor of the effectiveness of exercise in reducing the incidence of AF [1,5,22,23]. Although many population-based studies have been carried out so far, we still cannot see a very precise model for estimating the effect of minimal physical activity, depending on its condition and type, in relation to AF risk; however, the beneficial effects of exercise are unobtainable on the overall pattern of heart disease risk.…”
Section: Studies In the General Populationmentioning
confidence: 91%
“…Based on existing evidence, mild to moderate-intensity physical activity for 150 to 200 minutes per week (about half an hour per day), or aerobic exercise for 90-150 minutes per week (about 15-20 minutes per day), or achievement of cardiorespiratory fitness over 8 seems to be associated with a lower risk of AF [9]. However, it is strongly recommended to determine the desired duration and intensity of exercise in coordination with the medical practitioner [23], especially in individuals with other AF risk factors.…”
Section: Suggestions For Practicementioning
confidence: 99%
“…In the European guidelines, shared decision-making relating to the continuation of intensive or competitive sports participation is recommended, taking into account the underlying disease, the psychological impact of shocks, the potential risk for third parties, and the fact that intensive sport will trigger more appropriate and inappropriate shocks ( Class IIa, Level of evidence C ) ( 63 , 70 ). Empowerment of athletes with disorders with potential arrhythmic risk might have advantages such as allowing a more transparent and doctor–patient relationship, avoiding “doctor shopping” and acquiring more knowledge in “gray zone areas” (i.e., exercise in recipients of ICD) ( 71 ).…”
Section: Athletes With Potentially Arrhythmogenic Diseasesmentioning
confidence: 99%
“…Potential career-ending decisions are complex, involving medical, ethical, and legal issues, and can have severe psychosocial and economic consequences [ 81 ]. Giving an athlete the right to participate in the decision of whether or not to compete involves empowering them [ 82 ]. Three models of treatment decision-making are described with progressive levels of empowerment:…”
Section: Reviewmentioning
confidence: 99%